Exploration of the Role of Double Schiff Bases as Catalytic Intermediates in the Knoevenagel Reaction of Furanic Aldehydes: Mechanistic Considerations - van Schijndel, Jack; Canalle, Luiz Alberto; Molendijk, Dennis; Meuldijk, Jan (Synlett, 2018)
This paper presents mechanistic considerations on an efficient, green, and solvent-free Knoevenagel procedure for the chemical transformation of furanic aldehydes into their corresponding α,β-unsaturated compounds. In the proposed mechanism furanic aldehydes react with ammonia, released from ammonium salts, to form a catalytically active double Schiff base. The catalytic intermediates involved in the condensation step are characterized.
Keywords: furfural; 5-HMF; green Knoevenagel; catalytic intermediates; double Schiff base